Influence of drought stress during the grain-filling stage on malt main quality traits of barley - HONG Ye; ZHANG Guoping (浙江大学学报. 农业与生命科学版, 2022)
This experiment was carried out to investigate the effects of drought stress treatments during the grain-filling stage on the malt main qualities of the two barley genotypes, Zheda No. 9 (ZU9) (a cultivar) and XZ166 (a wild Tibetan barley accession), which differed greatly in the drought tolerance and malt quality, and had the similar heading and maturing stages. The results showed that drought stress significantly increased the malt protein and α-amino nitrogen contents, and the Kolbach index, and reduced malt extract rate and viscosity, with ZU9 being more largely affected than XZ166. Drought treatment at the early grain-filling stage (7 d after anthesis) caused much larger changes of all the examined malt qualities in ZU9 than in XZ166, while for the drought treatment at the middle grain-filling stage (14 d after anthesis), the changes of these quality traits were much larger in XZ166 than in ZU9. It may be concluded that drought stress occurred during the grain-filling stage had a great impact on malt quality, which should be addressed in breeding and agronomic management of malt. In the actual production, appropriate varieties should be selected according to the occurrence time of the drought, so as to avoid the drought stress during the critical period of quality formation.